PWM Dimming for High Brightness LED Based Automotive Lighting Applications - Muhammad Wasif Umar; Norzaihar Yahaya; Zuhairi Baharuddin (Institute of Advanced Engineering and Science, 2017)
In recent years, the use of high brightness LEDs has become increasingly accepted as light sources in mainstream vehicles. However, they are semiconductor devices and their electrical characteristics are completely different to the traditional lamps. The output luminous flux of an LED is determined by the forward current running through it. Hence they cannot be powered directly from the automotive battery using the conventional driving techniques. They require specialised driving circuits which can respond to the changing needs of the LEDs as their electrical properties change, while maintaining the uniform brightness. This paper discusses the importance of dimming for LED based automotive lighting applications. A boost type DC-DC switching converter with pulse width modulated (PWM) dimming control has been proposed. MATLAB/Simulink simulation package has been used to verify the theoretical predictions hence to provide a useful guide for design engineers and researchers.